Nerve Conductin Velocity & Amplitude of Action Potential in Sensory Peripheral Nerves of Upper & Lower Limbs in Normal Subjects - Husan Bano, Hyder Raza Nagy’, Sumera Gut (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objectives: To provide the reference el ectrophysiol ogical data for commonly tested sensory nerves of upper and lower limbs. Place & Duration: Experimental Observational Study, carried out in the Department of Physical Medicine and Rehabilitation, Jinnah Postgraduate Medical Centre, Karachi, from Nov. 2011 — Nov. 2013. Material and Methods: Nerve conduction data was recorded from normal healthy volunteer [n=80: males(m) n= 36 and females( f) n=44], age range (20-60yrs) with normal neurological examination and no known risk factor or symptoms to suggest the disease of peripheral nervous system. Subjects were further grouped: 20-30 years m (n=10 )4( in-16). 31-40 years m (n-10)4(n=12), 41-50 years in (n-10)4 (n=10) and 51-60 years m (n-6 )if (n=6 ). Radial nerve, sensory median (finger III), sensory ulnar (finger V) nerves ofupper limbs and Sural nerve of lower limb were studies using standard recording technique. The physiological variables recorded from these nerves include nerve conduction velocity (NCV) and amplitude of sensory action potential ( SAP). Data was analyzed statistically on SPSS version 17.0. Results: No statistically significant difference was found in conduction velocity and amplitudes of upper and lower sensory peripheral nerves by gender. However, a significant decrease in the NCV and SAP of radial nerve and sensory median was observed in both genders in the age group 51-60yrs. In the same age group a significant decrease in the NCV and SAP were observed in sensory ulnar and the rural nerve in males only, Conclusion: We designated the normative reference values of the sensory peripheral nerves in healthy subjects which have value to determine neuropathy in early stage of disease.